Shaoyao gancao decoction induces autophagy by modulating miR-21 and inhibiting the AKT/mTOR signaling pathway in adenomyosis-derived ectopic endometrial stromal cells - Lai, Huijie; Jia, Jinjin; Kuang, Zijun; Lu, Jie; Zeng, Yuyan (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceShaoyao Gancao Decoction (SGD) is a renowned traditional Chinese medicinal formulation widely utilized in Asia. It is particularly effective in treating spastic, painful, and inflammatory conditions, especially gynecological pain disorders. However, the underlying mechanisms of its action remain largely unexplored.Aims of the studyTo investigate the potential molecular mechanism by which SGD inhibits autophagy and apoptosis in ectopic endometrial stromal cells (EESCs), thereby elucidating the pathway responsible for its anti-adenomyosis effects.Materials and methodsFour types of tissues were collected for detection, including AM ectopic endometrium, AM eutopic endometrium, normal myometrium, and normal endometrium. Meanwhile, EESCs were cultured in vitro and divided into three groups: blank control group, blank serum group, and SGD-containing serum group. Autophagy in EESCs after microRNA-21 (miR-21) transfection was observed using a transmission electron microscope (TEM). Apoptosis of EESCs was detected by flow cytometry (FCM). A quantitative real-time polymerase chain reaction (qRT-PCR) assay was adopted to evaluate the expressions of miR-21 and phosphatase and tensin homolog (PTEN). For the expression of proteins related to the relevant signaling pathway, autophagy, and apoptosis, the Western blot technique was employed.ResultsIn ectopic endometria of AM, there was a significant increase in miR-21 mRNA expression as well as heightened activity within the phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) signaling pathway. Conversely, PTEN expression was found to be decreased. Additionally, autophagy-related protein levels were diminished while anti-apoptotic protein expression was markedly elevated (P < 0.01). Results from cell experiments indicated that treatment with SGD downregulated miR-21 mRNA expression along with p-AKT and p-mTOR protein levels (P < 0.01), while up-regulating PTEN mRNA expression (P < 0.01) in EESCs. Simultaneously, the expression of autophagy-related proteins was increased.ConclusionThe progression of AM is associated with autophagy inhibition in ectopic lesions. SGD can exert autophagy-promoting and pro-apoptotic effects in EESCs, and this process occurs by inhibiting the AKT/mTOR signaling pathway with miR-21 as the target. These findings unveil the potential novel molecular mechanisms from the perspective of microRNA by which SGD suppresses the growth of EESCs.